Action research in healthcare - Koshy, Elizabeth; Koshy, Valsa, 1945-; Waterman, H. (Heather); Sage eBooks (Los Angeles : SAGE, 2011)
This is a practical guide to using research for improving practice in healthcare contexts. Taking you through the process step-by-step, the book explains how to tackle each stage of your project - from planning the study and undertaking a literature review, through to gathering and interpreting data and implementing findings.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Action research in public health; Electronic books